UJI IMUNOMODULATOR BEBERAPA SUBFRAKSI EKSTRAK ETIL ASETAT MENIRAN (Phyllanthus niruri [L]) PADA MENCIT PUTIH JANTAN DENGAN METODA CARBON CLEARANCE - Yufri Aldi; Nisya Ogiana; Dian Handayani (Universitas Baiturrahmah, 2014)
Meniran has scientific name Phyllanthus niruri L..It uses to increase imun system of human body. Nonspecific of Imun system is first defendent to protect human body from microorganism, because it gives direct respon to antigen then it will destroy bacteria with phagocytosis process. Meniran extract is known can obstruct xanthin oksidase invitro, protect hepatocyte cell of liver from carbon tetrachloride and cytotoxity that induction with galaktosamin.To determined imunomodulator activity of some ethyl acetat extract subfraction of meniran (Phyllanthus niruri [L.]). Some ethyl acetat extract subfraction of meniran (Phyllanthus niruri [L.]) administered orally with single dose 100 mg/kg BB for eight group of subfraction and Tween 80 1% as control for 6 days. After 6 days subfractions have been conducted in white male mice with carbon clearance method. A value of Index Phagocytosis (IF) < 1 has imunosupressant activity and IF > 1 has imunostimulant activity. The increasing of phagositosis index with carbon clearance method showed the effect from each group of subfraction with control was unsignificant (P>0,05). The incerasing of leucocyte cell component especially for limfosit cell, eusinofil, and segmen neutrofil was significant for each group of subfraction (P0,05). The increasing of spleen limfosit cell showed optimal effect in subfraction number three (P